Recent development in graphene-reinforced aluminium matrix composite: a review - Md Ali, Afifah; Omar, Mohd Zaidi; Hashim, Hanizam; Salleh, Mohd Shukor; Mohamed, Intan Fadhlina (Walter de Gruyter GmbH, 2021)
Considerable attention has been given to graphene as a reinforcement material for metal matrix composite (MMC) because of its great potential for use in the automotive and aerospace industry. In general, the difficulty in achieving optimally improved properties can be attributed to poor wettability, agglomerations, and non-uniform distribution of reinforcement in the MMCs. Therefore, in terms of structural integrity, interfacial bonding, and its strengthening mechanism are important to achieve a high performance composite, which makes it imperative to discuss the integration of graphene into the alloy. The reinforcement mechanism of graphene-reinforced aluminium alloy has been evaluated in a limited number of studies, and this article examines current publications in this area. This article outlines three key topics related to the key challenges of graphene as a reinforcement material, the strengthening mechanism of graphene in a metal matrix, and the factors limiting the properties enhancement. Lastly, future works and recommendations addressed are summarized. The review presented aims to benefit to a wide range of industries and researchers and serve as a resource for future scholars.